Revealing the Unique Properties of Platinum(II) Complexes with Bidentate Bis(o‐carborane) Ligands. Issue 1 (10th January 2018) - Li, Wenqian; Yan, Xi; Zhang, Huize; He, Rongxing; Li, Ming; Shen, Wei
Abstract : The phosphorescent transition‐metal complexes (PTMCs) of the bidentate 1, 1′‐bis( o ‐carborane) (bc) ligand were theoretically studied for the first time. Density functional theory (DFT) and time‐dependent density functional theory (TD‐DFT) were utilized to elucidate the relationship between the structures and properties of complexes with different binding modes and increasing numbers of carboranes. Compared with previous common bidentate ligands, the introduction of bulky carboranes enormously changes the electronic structures, electroluminescence properties (including phosphorescence emission band, radiative and non‐radiative decay processes), and intermolecular interactions of the complexes. The various binding modes between the bc ligand and the metal center only influence the degree of structural distortion and the intermolecular interactions. Based on our analysis, a series of complexes were designed by introducing different substituents at the B(12) position to tune the phosphorescence properties of these complexes, which reveals a potentially new avenue for the design of novel PTMCs to be used in organic light‐emitting diodes (OLEDs). Abstract : The phosphorescence properties of the 1, 1′‐bis( o ‐carborane) ligand coordinated to Pt II were investigated theoretically. The introduction of bulky carboranes enormously changes the electronic structure and electroluminescence properties. This study reveals a potentially new avenue for the design of novel phosphorescent transition‐metal complexes (PTMCs) to be used in organic light‐emitting diodes (OLEDs).